Exploring the effect of Covid-19 on usage of virtual library services at the University for Development Studies Library - Akeriwe, Miriam Linda; Bumbie-Chi, Deborah Mwintierong; Alua, Mary Ann (Ghana Library Journal, 2024)
Providing access to resources for teaching, learning and research is core to services rendered by libraries and librarians. The advent of the novel Coronavirus onto the global landscape has had major implications for libraries. This study was carried out to explore the effect of the Covid-19 pandemic on the usage of virtual services and platforms at the University for Development Studies (UDS) Library. The study adopted a quantitative method by conducting a comparative analysis of patrons’ usage of virtual library services prior to and during Covid-19. The usage statistics from the UDS library’s various virtual service delivery platforms constituted the data for this study. The findings revealed significant increases in usage of the virtual library’s services across the selected platforms and usage patterns, which provides statistical data on changes in usage of virtual platforms for library service delivery to enhance planning. The way forward is to intensify trainings to ensure that users have access to these platforms and services while addressing limitations that interrupt service provision.